Metro Network Communication Configuration based on Mean Value - DONG Lifang; MU Junbin; ZHANG Chuang; ZHU Zhongchao; Gao Xinghua (机车电传动)
The communication bus load factor and the degree of bus load balancing directly influenced the stability of metro vehicleperformance. A method of metro vehicle communication configuration, which was based on the mean value and automatic offset forfinally communication configuration list, was proposed, and the network load was analyzed. This communication configuration designwas reasonable and feasible, which could guarantee the balanced distribution of the communication load and improve the stability of thecommunication network.